Remaining silent: The ongoing presence of silent films on cinema programmes in Brno between 1930 and 1936 - Večeřa, Michal (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2023)
The production of silent gilms in Czechoslovakia ended shortly after the advent of sound technology at the very end of the 1920s. The number of available silent films steadily decreased from that point on, yet some cinemas decided to continue to include them in their programming, even though they had sound equipment. The article analyses the scheduling of silent films in the specific case of two cinemas from the periphery of Brno, the second-largest city in Czechoslovakia. On the exhibitors’ side, there was a visible tendency to screen films 1) approximately two years from the premiere and 2) older with renowned stars or plot. This surprising presence of silent films in cinemas leads to the question: “Why were they still scheduled”? The answer lies both in the cinema owners, for whom silent films were a cheaper commodity, and in the audiences, who did not necessarily demand screenings of new sound films.